2012
DOI: 10.1128/jvi.06169-11
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes Mediated by MicroRNA miR29 Activate Cyclooxygenase 2 and Lambda-1 Interferon Production during Viral Infection

Abstract: Lambda-1 interferon (IFN-1) and cyclooxygenase-2 (COX-2) were reported to play an important role in host antiviral defense. However, the mechanism by which IFN-1 and COX2 are activated and modulated during viral infection remains unclear. In this study, we found that expression of both circulating IFN-1 and COX2-derived prostaglandin E2 (PGE2) was coordinately elevated in a cohort of influenza patients compared to healthy individuals. Expression of IFN-1 was blocked by a selective COX2 inhibitor during influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 47 publications
9
74
0
Order By: Relevance
“…Although the effects on methylation following transfection of miR-29b are rapid, these observation are supported by previous publications highlighting changes in PGE 2 production following 24-h transfection of A549 cells with siRNA against DNMT1, DNMT3a, or DNMT3b (20) and DNMT activity following 48-h transfection of a lung fibroblast cell line with siRNA against DNMTs (17). Furthermore, a study investigating gene methylation in breast cancer cells following transfection with miR-29b showed significant changes in methylation following 72-h transfection of pre-miR-29b (52).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Although the effects on methylation following transfection of miR-29b are rapid, these observation are supported by previous publications highlighting changes in PGE 2 production following 24-h transfection of A549 cells with siRNA against DNMT1, DNMT3a, or DNMT3b (20) and DNMT activity following 48-h transfection of a lung fibroblast cell line with siRNA against DNMTs (17). Furthermore, a study investigating gene methylation in breast cancer cells following transfection with miR-29b showed significant changes in methylation following 72-h transfection of pre-miR-29b (52).…”
Section: Discussionsupporting
confidence: 86%
“…As mentioned earlier, miR-29b has putative binding sites in the 3=UTR of DNMT3a and DNMT3b. A previous study confirmed these binding sites and showed direct binding of miR-29b on the 3=UTR (20). A previous study also showed that miR-29b can indirectly downregulate DNMT1 by targeting Sp1 (21).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In a previous study, they show that miR-29 suppresses DNMT activity and thus induces expression of COX-2 and PGE 2 . These findings reveal a novel proinflammatory cascade in the control of influenza A virus infection (31).…”
Section: Discussionmentioning
confidence: 77%